Immunocytochemical analysis of AlgP (Hp1), a histonelike element participating in control of mucoidy in Pseudomonas aeruginosa. - Deretic, V (1992)
AlgP, a protein with an unusual carboxy-terminal domain resembling the tails of eukaryotic H1 histones, was detected in whole-cell extracts and within the cells of Pseudomonas aeruginosa by using immunoblotting and immunoelectron microscopy analyses. One known function of AlgP is its participation in the transcriptional activation of the algD gene. This is a pivotal step in the establishment of mucoidy in P. aeruginosa; mucoidy is a critical virulence factor expressed during respiratory infections in patients with cystic fibrosis. Polyclonal and monoclonal antibodies were raised against a synthetic 50-mer peptide containing two sets of six tandem repeats of the motif Lys-Pro-Ala-Ala (and its single-amino-acid substitution variants), based on the sequence of the algP gene from the standard genetic strain PAO. Western immunoblots with these antibodies and total protein extracts from P. aeruginosa revealed two polypeptides that reacted with the antibodies in all of the P. aeruginosa strains tested. The detected polypeptides displayed strain-dependent variability in their electrophoretic mobility, in accordance with the previously noted variability of the algP repeats at the DNA level. In strain PAO, the recognized polypeptides had apparent masses of 46.4 and 41.6 kDa. Immunoelectron microscopy revealed that AlgP is an intracellular protein with a wide distribution suggestive of its more general role. To indicate that fact, AlgP is given here an alternative name, Hp1. Since AlgP (Hp1) is a eubacterial histonelike element displaying sequence and domanial similarity with eukaryotic H1 histones, these findings may have implications on the understanding of the organization of the prokaryotic nucleoid and its role in the control of gene expression and bacterial virulence.